EMPLOYEE PERFORMANCE IMPROVEMENT THROUGH RELIGIOUS VALUES AND QUALITY OF COMMUNICATIONS AS WELL AS PERSONAL INTEGRITY (Case Study in PoLSUSKA Daop 5 Purwokerto) - Achmad Zahid (IJIBE (International Journal of Islamic Business Ethics), 2017)
The purpose of this study is to examine a model in which religious values and communication quality predict personal integrity and employee  performance.  A  total  of  129  respondents fromPolsuska Daop 5 Purwokertocompleted questionnaires. Results from structural equation modeling based smartPLS 3.0 confirmed that religious values and communication quality were positively related to personal integrity and employee performance. Furthermore, the result revealed that personal integrity was positively related to employee performance. Keywords: Religious values, Communication quality, Personalintegrity, Employee performance